(untitled) (Journal of Economic Research & Business Administration, 2017)
In the modern world, human resources are the most valuable asset of the company and crucial instrument of organization’s success. For effective exploitation of human resources, it is vital to understand how appropriately execute the managing process over people. Such managing activity is quite complex due to peculiar nature of its object – person. Hence, in order to determine the effective system of personnel management for successful performance of the company, it is equally important to understand what exactly constitutes human resource management. Unfortunately, despite the fact that a considerable research has been done in this area, there are still significant doubts about what precisely composes human resource management and controversies around the meaning of the term. Therefore, the author of the article examined and analyzed the nature of human resource management, focusing on a number of existed definitions, views, and approaches suggested by various prominent foreign and local scholars and experts in the field of human resource management. The tasks of the study lie in consideration of a significant number of definitions of HRM, interpretations, and approaches existed in current foreign and national literature; and to determine the definition and meaning of human resource management practices. The analysis of various existing definitions, interpretations and approaches to human resource management were made. As a result of the research, it has become possible to clarify the meaning and essence of human resource management, also by summarising all considered definitions one comprehensive definition was proposed. In its turn, this will help theadministration to develop the efficient system of HR management in companies and fortunately, will improve the implementation of such practices in the organizations.